PENGARUH LINGKUNGAN EKSTERNAL TERHADAP MINAT BERWIRAUSAHA RUMAH MAKAN DI KELURAHAN PASAR TELUKDALAM - Waruwu, Nesli Irawati (Universitas Nias Raya, 2024)
The purpose of this study was to determine the influence of the external environment on the entrepreneurial interest of restaurants in Pasar Telukdalam Village. The type of research is a quantitative type that is causal (cause and effect), with the population and sample being restaurants in Telukdalam Village as many as 32 people. Data collection techniques are questionnaires and documentation techniques. The analysis method is a simple regression analysis with a value of Y=9.598+0.777X. Based on the results of the hypothesis testing study with a calculated value of 7,020>ttable 1,697, it can be concluded that there is an influence of the external environment on the entrepreneurial interest of restaurants in Pasar Telukdalam Village. The suggestions of this study are (1) Restaurants should provide inadequate facilities such as places of worship, toilets, and wifi so that consumers are comfortable. (2) Restaurant business owners must have motivation so that their business grows.